Coordinating Educational Initiatives Processed By a Variety of Program Actors within the Primary Health Care Setting - Olalotiti- Lawal; Modupe Olufunmilola; Bamidele James Olusegun; Dr Ogunsola Ayowole Elijah; Jayeoba Olufunke Felicia; Ayinde Abayomi Oluwasegun (Journal of Science in Medicine and Life, 2023)
Introduction: The field of health education is dedicated to promoting healthy behaviors (Green et al., 1980; Tone and Tilford, 1994). Notable researchers, including Green et al. (1980), Sunderland (1979), French and Adams (1986), Smail (1992), and Macdonald (1994), have contributed significantly to health education research. Publications like Jinadu and Adetugbo (1992), Das Gupta, Gauri, and Khemani (2003), and the Nigerian Demographic and Health Survey (2008) have provided valuable insights, especially in developing countries like Nigeria. Alternatively, the literature by distinguished health behavior researchers extensively highlights instances of inadequately coordinated or confused educational activities, serving as potential catalysts for health misinformation. As emphasized by Houlden et al. (2021), this complicates endeavors to promote healthy decision-making. The understanding of the intricacies in these scenarios is inherently linked to the accessibility of dependable data. The insufficiency of data that assesses the effects of health education in developing nations, exemplified by Nigeria (FMOH, 2004), seems to impede efforts towards policy reform. The efficacy of health education is consistently under scrutiny due to the lack of well-defined methodologies, frameworks, and tangible program achievements. Within the primary healthcare (PHC) setting, various terms such as "social mobilization" and "Information Education Communication (IEC)" are casually employed, contributing to a complex interplay. There are deficiencies in the management processes of health education, and its alignment with PHC programs is not well-defined. Policies often prioritize program acceptance rather than the specific behavioral and non-behavioral impacts. The Ward Minimum Health Care Package (WMHCP) aims to deliver ward-level services but lacks clear health education strategies. This study addresses the disarray in PHC health education, with a focus on integrated maternal, newborn, and child health (IMNCH) in Ekiti State. It aims to explore how community needs influence health education practices, a topic of global debate (Brieger and Edozien, 1982; Ransome-Kuti et al., 1990; Macdonald, 1994). Management elements play a vital role in strengthening health education standards and achieving measurable results, which is also relevant in the Nigerian context. Objectives: This study aims to identify the educational efforts undertaken by various program stakeholders operating within the primary healthcare setting. A primary focus is placed on critically evaluating the prevailing organizational models within educational interventions to identify potential deficiencies and inefficiencies hindering the optimal delivery of health education services. Additionally, the study aims to quantify these gaps through statistical analysis, shedding light on specific areas requiring immediate attention and intervention. Data Analysis Method: The research methodology employs a rigorous approach, including well-structured surveys and in-depth interviews with health education professionals across diverse tiers of the PHC framework. Quantitative data undergoes comprehensive statistical analysis, revealing essential percentages and numerical trends. Qualitative responses are thematically analyzed in detail, providing nuanced insights into challenges and potential solutions. Results: The empirical findings of this study shed light on critical aspects of the PHC health education landscape. The study reveals that 72% of health education professionals are female, indicating a significant gender disparity within the workforce. Remarkably, 89% of these professionals received training primarily on the job or through workshops, underscoring the absence of formal educational protocols. The study also finds that 68% of health education professionals operate within the dispersed organizational model, while 22% adopt coexisting models, and 10% employ specialist approaches. Furthermore, 56% of respondents express a reliance on external partners for planning, highlighting a concerning dependency on non-internal resources. Strikingly, 85% of health education professionals lack concrete selection criteria for educational targets, underscoring a critical gap in strategic planning. Conclusion: The comprehensive analysis emphasizes the urgent need for standardized guidelines, strategic planning, and coordinated efforts to enhance the efficacy and impact of health education interventions within PHC settings. The numerical data presented underscores the seriousness of the situation, necessitating immediate policy revisions and targeted interventions. Recommendations: Urgent policy revisions are imperative, with a focus on gender equality, standardized training, and structured planning protocols for health education professionals. The national health policy should prioritize comprehensive strategies for health education, emphasizing internal coordination and reduced dependence on external partners. Additionally, substantial investments in capacity-building initiatives, particularly formal education for health education professionals, are vital to bridge the training gap.